Antimicrobial resistance (AMR): A major challenge for the aquaculture industry in Bangladesh - Rheman, Shafiq; Delamare-Deboutteville, Jerome; Mohan, Chadag V. (WorldFish, 2022)
This fact sheet is to provide up-to-date information supported by scientific evidence on the importance of antimicrobial use (AMU) and antimicrobial resistance (AMR) in aquatic food systems of Bangladesh to support all relevant stakeholders to engage in interventions and actions to minimize AMU and promote One Health initiatives through responsible and sustainable aquaculture practices.